The relation of disgust proneness/sensitivity and ageism. (July 2021) - Nicol, Adelheid A.M.; De France, Kalee; Gagnon, Mathieu
Abstract: Increasing awareness of the prevalence and implications of ageism has led researchers to examine the factors contributing to this form of prejudice. Scant attention has been paid to the role of emotions in the development and formation of negative attitudes towards older adults. Our research explored this issue by focusing specifically on propensity to, and sensitivity towards, the emotion of disgust. Two self-report studies were conducted. In the first study, regression analyses were employed to determine whether there was a relation between disgust proneness/sensitivity and ageism in a sample of 308 participants aged 18 to 30. In a second study we explored the possibility of an indirect relationship between disgust proneness/sensitivity and ageism mediated by perceived vulnerability to disease and aging anxiety in a sample of 349 participants aged 18 to 30. While we found no evidence of a direct relationship between disgust proneness/sensitivity and ageism in the first study, results from the second study showed a significant indirect effect between disgust proneness/sensitivity and ageism, mediated by both perceived vulnerability to disease and aging anxiety. This relationship may be understood using an evolutionary account which involves pathogen avoidance and a Terror Management account which involves anxiety about death.